2019
DOI: 10.1177/0146167219838790
|View full text |Cite
|
Sign up to set email alerts
|

Testing Hypersensitive Responses: Ethnic Minorities Are Not More Sensitive to Microaggressions, They Just Experience Them More Frequently

Abstract: Racial microaggressions have attracted significant empirical attention and have been associated with profound negative effects. However, some argue against the importance of microaggressions arguing that (some) responses to microaggressions merely reflect “hypersensitivity” to trivial events among certain ethnic minority individuals. Three studies tested this hypersensitivity hypothesis. In two cross-sectional studies with dissimilar samples ( N1 = 130, N2 = 264), ethnic minorities reported experiencing more m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 85 publications
(185 reference statements)
3
46
1
Order By: Relevance
“…These findings broadly corroborate the statistical association between microaggressions and mental health, and they suggest that this correlation is likely to be small to medium in magnitude. Contrary to a core presupposition of the MRP (Sue et al, 2007) that has been endorsed by a number of other scholars (e.g., West, 2019), there was no support for the contention that the more subtle the microaggression, the greater the harm. As the authors observed, few studies examined whether microaggressions afford incremental validity above and beyond overt indicators of prejudice, so the extent to which microaggressions per se are tied to adverse mental-health outcomes remains unclear (see also Lilienfeld, 2017a).…”
Section: The Causal Status Of Microaggressionscontrasting
confidence: 62%
See 1 more Smart Citation
“…These findings broadly corroborate the statistical association between microaggressions and mental health, and they suggest that this correlation is likely to be small to medium in magnitude. Contrary to a core presupposition of the MRP (Sue et al, 2007) that has been endorsed by a number of other scholars (e.g., West, 2019), there was no support for the contention that the more subtle the microaggression, the greater the harm. As the authors observed, few studies examined whether microaggressions afford incremental validity above and beyond overt indicators of prejudice, so the extent to which microaggressions per se are tied to adverse mental-health outcomes remains unclear (see also Lilienfeld, 2017a).…”
Section: The Causal Status Of Microaggressionscontrasting
confidence: 62%
“…Indeed, because NE is linked to more threatening interpretations of ambiguous stimuli of many kinds, including homophones, sentences, social scenarios, workplace stressors, children’s behavior, and bodily sensations (e.g., Stegen et al, 2000; Watson & Clark, 1984; Watson & Pennebaker, 1989), it would be remarkable if microaggression items were entirely immune to this well-replicated tendency within each race. Hence, Williams’s assertion that I invoked a “cultural-deficit model” (p. 4) of microaggressions reflects a fundamental misunderstanding of my position (for a similar error, see West, 2019).…”
Section: Reliance On Self-report and The Role Of Negative Emotionalitymentioning
confidence: 98%
“…Nevertheless, within POC groups, racial microaggression experiences were linked to psychological outcomes over and above trait neuroticism [ 29 , 30 ]. Research also showed that POC’s health outcomes were disproportionately affected by discrimination and microaggression not because of people’s hypersensitivity to racism; rather, POC were more likely to experience differential treatment relative to Whites [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worse yet, microaggressions remain unnoticed and unaddressed because there is no easy way (for the perpetrator or the recipient) to disarm them after they have occurred (Sue et al, 2019). For recipients of microaggressions in particular, reacting in the moment incurs high social costs (Kaiser & Miller, 2001) and risks being perceived as being hypersensitive (West, 2019). As such, recipients of microaggression typically "freeze" in the moment (Goodman, 2011), wish they could have spoken up after the moment has passed (Shelton et al, 2006), and are ridden with guilt and anxiety for their own paralysis (Sue et al, 2019).…”
Section: Microaggression As Covert Discriminationmentioning
confidence: 99%